Market Definition: Use and Abuse - Dennis W. Carlton (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
A "market" can be rigorously and precisely defined quantitatively, but the information to do so is typically not available. Instead, markets are often defined based on qualitative information, leading to the possibility of errors. I make some practical suggestions to mitigate such errors. When markets are correctly defined, it is the change in market shares that is central to the antitrust analysis, though this is not how courts typically use market definition and shares to analyze Section 2 cases. Unfortunately, there is only a weak link between change in market share and change in competitive performance, and that is why market definition and the use of market shares are very crude tools of analysis. That is why their best use is as safe harbors to quickly screen out frivolous cases from those where the economic forces governing industry behavior need to be carefully studied. But, I explain why even this use of market definition and market shares can be problematic in Section 2 cases.
Keywords: 330